The correct expression that shows \( x \) and its opposite are \( 0 \) is:
x + (−x) = 0
This expression shows that when you add \( x \) and its opposite (which is \( -x \)), the result is \( 0 \).
Which expression shows x and its opposite are 0?(1 point)
Responses
x+(−1x)=0
x plus left parenthesis negative Start Fraction 1 over x End Fraction right parenthesis equals 0
x+x=0
x plus x equals 0
x+(1x)=0
x plus left parenthesis Start Fraction 1 over x End Fraction right parenthesis equals 0
x+(−x)=0
1 answer
The correct expression that shows \( x \) and its opposite are \( 0 \) is:
x + (−x) = 0
This expression shows that when you add \( x \) and its opposite (which is \( -x \)), the result is \( 0 \).